Bringing it all back home: Early Ceramic period residential occupation at the Kinney Spring Site (5LR144c), Larimer County, Colorado - Perlmutter, Benjamin, author; LaBelle, Jason M., advisor; Van Buren, Mary, committee member; Fish Kashay, Jennifer, committee member (Colorado State University. Libraries, 2015)
The Kinney Spring site (5LR144c) was excavated by the Colorado State University archaeological field school during the summers of 1983 through 1985. Rich cultural deposits were recovered which indicated reoccupation of the site from the Middle Archaic period through the Early Ceramic period, however the densest concentrations of artifacts were associated with Early Ceramic occupations (A.D. 150-1150). This research focuses on the Early Ceramic period at the site. The first part of this thesis aims to define the Late Prehistoric period chronology for the site by first defining where the Late Prehistoric component begins in the stratigraphic column. Analysis determined that there is sparse evidence for Middle Ceramic and possibly Protohistoric period occupation of the site based on diagnostic artifacts, although this is not sufficient to define any Middle Ceramic or Protohistoric components. The second part of this thesis explores the Early Ceramic component in greater detail. Artifact accumulations and radiocarbon dates suggest that Kinney Spring was reoccupied multiple times during the Early Ceramic period, suggesting that the site was an important part of the regional Early Ceramic era settlement system. Multiple lines of evidence suggest that occupational intensity increased here during the Early Ceramic, likely in response to increasing regional population pressure.
Keywords: Early Ceramic; architecture; Late Prehistoric